Torque and pitch control for wind energy conversion system using sliding mode approach - Subba Rami Reddy, C; Suresh Ogeti, Pedda; Gireesh Kumar, D; Bhoopal, N (International Journal of Engineering and Technology, 2018)
The integration of wind energy with the grid is one of the major challenges as the wind energy depends upon the most fluctuating wind speeds. Therefore it requires a stringent methodology to control and maintain the stability of power system. This paper presents the torque and pitch control of Wind Energy Conversion System (WECS) that implements the variable speed Doubly Fed Induction Generator (DFIG) using Sliding Mode (SM) approach. For the speeds above the rated wind velocity, pitch control technique has been implemented and below the base speed torque control technique has been applied. The limitations of pitch actuator are compensated by the torque control of induction generator. The modeling and simulation of WECS with sliding mode control (SMC) scheme is carried out using MATLAB SIMULINK environment. The performance parameters such as pitch angle, active power, reactive power and rotor speed are compared for the Proportional plus Integral (PI), Linear Parameter Varying (LPV) and SMC schemes. Simulation results confirm that the performance of SM control is superior in terms of pitch, speed, active and reactive power compared to PI and LPV controllers.Â Â